Hubungan Umur Dan Paritas Dengan Ruptur Perineum Pada Persalinan Normal Di Puskesmas Padasuka Kota Bandung Periode 2015-2016 - Sitepu, Sitepu, T.J; Putriani, Putriani, I (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2019)
Rupture perineum is a lot of problems that still occurs in normal labor. The birthingmothersexperienced a ruptured perineum as much as 520 (63%) at Puskesmas Padasuka the City of Bandung.To know the correlation between age and parity with ruptured perineum at normal labor inmPuskesmas Padasuka the City of Bandung Period 2015-2016. Type of analytic research with cross sectional design research. Sample selection technique used is total sampling technique, that the entire sample into the subject of research as much as 520 cases of pervaginam labor from 2015-2016. The highest incidence of ruptured perineum in the age group 20-35 years were 399 (76.7%), age <20 years were 45 (8.7%) and multipara parity were 353 (67.9%), grandemultipara were 14 (2.7 %). There was a significant correlation between age to ruptured perineum with p-value 0.000 (α <0,05) and there was a significant correlation between parity to ruptured perineum with p-value 0,000 (α <0,05) in Puskesmas Padasuka the City of Bandung.